What makes up effective teaching? A Perceptual Approach to Determining Teacher Effectiveness - NATIVIDAD, CRISTINA B. (International Journal of Psychosocial Rehabilitation, 2020)
This paper discusses the different factors that play an important role in teaching effectiveness. It further discusses how different or similar teachers and students perceive teachers to be contributing to the effectiveness of teaching. It, therefore, looked into the profile of eight teachers and 250 first year college students who were the respondents of this study. In addition, it determined the perception of both groups of respondents in terms of the different factors that make up effective teaching. This study utilized the descriptive method, simple frequency count, weighted mean, and t-test to know the differences in the perceptions of the respondents. The results showed that the students perceive their teachers as “very good” as far as teaching effectiveness is concerned. The study also revealed that the teacher-respondents see themselves as “excellent” in almost all of the descriptors for the factors that make up effective teaching. The researcher concludes that there is no significant difference in the perceptions of both groups of respondents as far as teaching effectiveness is concerned. Therefore, the only recommendation that the researcher can make is that teachers should improve how they carry themselves physically as it came out in the findings that teachers, as well as students, perceive themselves (referring to the teacher) as “good” only in wearing make-up and trendy clothing.